ASSESSMENT OF THE AVAILABILITY OF MEDICAL SUPPORT FOR ATHLETES IN THE REGIONS OF THE SIBERIAN FEDERAL DISTRICT - Shilko T.A.; Popova E.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the level of accessibility of sports medicine in the regions of the Siberian Federal District. Methods and structure of the study. Content analysis of data on medical services for athletes in the regions of the Siberian Federal District, semi-structured interviews with athletes in the Tomsk region were carried out. Results and conclusions. A large imbalance was revealed in the number of medical centers in different regions of the Siberian Federal District. The share of the number of organizations shows interregional differences in the availability of medical care for people involved in sports, more than twice.